Oncoproteins E6 and E7 upregulate topoisomerase I to activate the cGAS-PD-L1 pathway in cervical cancer development - Luo, Ying; Niu, Mengda; Liu, Yanfei; Zhang, Miaochang; Deng, Yuanyuan; Mu, Dan; Xu, Junfen; Hong, Shiyuan (Frontiers in Pharmacology, 2024)
Background: Cervical cancer (CC) stands as a significant health threat to women globally, with high-risk human papillomaviruses as major etiologic agents. The DNA damage repair (DDR) protein topoisomerase I (TOP1) has been linked to various cancers, yet its distinct roles and mechanisms in CC are not fully elucidated. Methods: We investigated TOP1 expression in cervical intraepithelial neoplasia (CIN) and CC tissues utilizing qRT-PCR and IHC, correlating findings with patient prognosis. Subsequent knockdown studies were performed in vitro and in vivo to evaluate the influence of TOP1 on tumor growth, DNA repair, and inflammatory responses. Results: TOP1 was highly expressed in CIN and CC, negatively correlating with patient prognosis. Inhibition of TOP1 impeded CC cell growth and disrupted DNA repair. TOP1 was shown to regulate tumor-promoting inflammation and programmed death-ligand 1 (PD-L1) production in a cGAS-dependent manner. HPV oncoproteins E6 and E7 upregulated TOP1 and activated the cGAS-PD-L1 pathway. Conclusions: TOP1 acts as a DNA repair mediator, promoting CC development and immune evasion. Targeting the TOP1-cGAS-PD-L1 axis could be a potential therapeutic strategy for CC.